Spermidine - a predictor for neurological outcome and infarct size in focal cerebral ischemia? - Els, Thomas; Bruckmann, Jochen; Röhn, G.; Daffertshofer, Michael; Schulte Mönting, J.; Ernestus, R.-I.; Hennerici, Michael G. (Stroke, 2001)
Background and Purpose—Polyamines are mainly restricted to the intracellular space. During focal cerebral ischemia, polyamines are released from the intracellular compartment. Experimental studies have implicated a marked elevation in brain tissue and blood. The aim of our study was to investigate whether the elevation of polyamines in the blood of patients with focal cerebral ischemia correlates with the clinical outcome and the infarct volume.Methods—Polyamines were measured in 16 patients with focal cerebral ischemia and in 8 healthy control subjects. Blood samples for polyamine measurement were taken at admission and at fixed time points for the next 28 days. Polyamines were analyzed in red blood cells by a high-pressure liquid chromatography system. Clinical findings were recorded with the NIH Stroke Scale score. Volume of infarction was analyzed from cranial CT at admission and on days 4 to 6 after ischemia.Results—A significant increase of the spermidine level in the peripheral blood could be observed in all patients with focal cerebral ischemia as compared with control subjects (P<0.01), starting with the admission. Spermidine values correlated positively with the clinical outcome at several time points in the first 48 hours (r=0.90 to 0.40; P<0.01) and with the infarct volume in cranial CT on days 4 to 6 (r=0.91; P<0.01).Conclusions—As hypothesized from experimental data, polyamine levels in blood increase in patients after focal cerebral ischemia. The results indicate that the peripheral spermidine level is closely associated with the clinical outcome as well as with the infarction volume. Therefore, polyamines may be used as a novel predictor for the prognosis of patients with focal cerebral ischemia.
Gesehen am 31.03.2021